Uso do resíduo de PEAD reforçado com fibras da folha do abacaxizeiro como alternativa sustentável na elaboração de módulos de Cobogó - Vale, Thalita Beserra do (2023)
In this study, the feasibility of using recycled high-density polyethylene (HDPErec) reinforced with pineapple leaf fibers (PALF) as a non-structural architectural component for "Cobogó" was investigated as a sustainable alternative in the built environment. PALFs were extracted using a machine called the "paraibana" or agave fiber extractor, and the processing for PALF incorporation with HDPErec involved the extrusion method. Two PALF concentrations, 0.5% and 1%, were utilized. Subsequently, evaluations of the material's physical, mechanical, and thermal properties were conducted. The results revealed that the 0.54% ash content of PALF indicated a high degree of fiber purity and quality, positively influencing the final element's properties. Concerning tensile strength, the sample with HDPErec+1%PALF demonstrated superior performance, suggesting that the plant fiber acts as a filler, influencing the mixture's compaction and, consequently, positively impacting mechanical properties. Therefore, the incorporation of 1% PALF resulted in more satisfactory outcomes for use in the built environment and architectural elements, and was selected for the development of the Cobogó prototype. In conclusion, this research highlights the potential for utilizing PALF, often discarded despite its excellent mechanical properties, in combination with HDPErec, a commonly used material, to create sustainable materials.